Osteotomies for the Management of Medial Compartment Defects of the Knee - Grimm, Nathan L.; Levy, Benjamin J.; Jimenez, Andrew E.; Arciero, Robert A. (The Journal of Knee Surgery, 2020)
For nearly three-quarters of a century the proximal tibia osteotomy has been used as an effective treatment for cartilage injuries of the knee. Over this same timeframe several advancements have been made in our diagnostic, preoperative planning, and technical execution of this procedure. As such, good-to-excellent short-, mid-, and long-term outcomes have been reported. Since its inception, the most important step in deciding on this procedure is identifying the ideal candidate. This candidate should be a young patient (<55 years old), active, with isolated medial compartment arthrosis without significant comorbidities. With appropriate patient selection and careful preoperative planning, the patient should achieve excellent results and high satisfaction.
Keywords: knee; osteotomy; tibia; high tibial osteotomy; sports